2020
DOI: 10.1038/s41598-020-65705-7
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive profile of multi-sensory imagery, memory and dreaming in aphantasia

Abstract: For most people, visual imagery is an innate feature of many of our internal experiences, and appears to play a critical role in supporting core cognitive processes. Some individuals, however, lack the ability to voluntarily generate visual imagery altogether-a condition termed "aphantasia". Recent research suggests that aphantasia is a condition defined by the absence of visual imagery, rather than a lack of metacognitive awareness of internal visual imagery. Here we further illustrate a cognitive "fingerprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
186
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(260 citation statements)
references
References 29 publications
34
186
3
2
Order By: Relevance
“…36 Early support for this claim is found in a recent study on aphantasia from Dawes et al (2020), who report that 'aphantasic individuals also reported experiencing lower awareness and control during their dreams [compared to control subjects]' (6). The most relevant phenomenon here of course are lucid dreams in which the subject is able to control and manipulate her visual dream imagery to some degree (whether or not lucid dreams where insight is present but not control could be included in this sort of study will largely depend upon the-currently open question-of know exactly insight should be understood, especially with respect to mental agency-Voss 2016; Kühle 2014).…”
Section: Aphantasia and Lucid Dreaming: A Testable Empirical Hypothesismentioning
confidence: 99%
See 3 more Smart Citations
“…36 Early support for this claim is found in a recent study on aphantasia from Dawes et al (2020), who report that 'aphantasic individuals also reported experiencing lower awareness and control during their dreams [compared to control subjects]' (6). The most relevant phenomenon here of course are lucid dreams in which the subject is able to control and manipulate her visual dream imagery to some degree (whether or not lucid dreams where insight is present but not control could be included in this sort of study will largely depend upon the-currently open question-of know exactly insight should be understood, especially with respect to mental agency-Voss 2016; Kühle 2014).…”
Section: Aphantasia and Lucid Dreaming: A Testable Empirical Hypothesismentioning
confidence: 99%
“…13 Whilst it is well known that introspective reports regarding the vividness of mental imagery vary significantly amongst groups of individuals (McKelvie 1995;Phillips 2014), aphantasia is characterised by subjects-'aphantasics'-who typically describe themselves as not just as having mental imagery of a reduced vividness, or impaired capacities for mental imagery generation limited to certain visual kinds, but as lacking the capacity to generate (typically visual) mental imagery altogether. 14 The work on aphantasia, mental imagery and their neural bases is ongoing (Dawes et al 2020;Winlove et al 2018;Fulford et al 2018), however, the condition has been documented in a series of recent studies (Zeman et al , 2015 which aim to identify its central neurobehavioural features. 15 Produced as part of 'The Eye's Mind' AHRC Project at the Medical School at the University of Exeter, the first examines a form of imagery generation disorder exemplified in a single patient-MX-who lost the ability to generate visual imagery abruptly, aged 65, four days after a coronary angioplasty (see .…”
Section: Aphantasia and Dreamingmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the overlap between visual perception and visual imagery, researchers have derived a measure of the sensory strength of visual images whereby the extent to which imagining one of two stimuli biases the subsequent perception of that stimuli presented in a binocular rivalry paradigm (Keogh & Pearson, 2017b;Pearson, Clifford, & Tong, 2008). Importantly, studies have shown that while those with Aphantasia score significantly lower on self-report measures of visual imagery and measures of imagery sensory strength compared to controls they report intact spatial imagery (Keogh & Pearson, 2017a) and spatial memory (Dawes, Keogh, Andrillon, & Pearson, 2020). Specifically, on the Object-Spatial Image questionnaire (Blajenkova, Kozhevnikov, & Motes, 2006) whereby object imagery is measured with questions such as "I can close my eyes and easily picture a scene that I have experienced" and spatial imagery is measured with questions such as "I can easily rotate 3D geometric figures", those with Aphantasia reported significantly lower object imagery compared controls, however their scores on spatial imagery were not different from controls (Keogh & Pearson, 2017a).…”
Section: Introductionmentioning
confidence: 99%